Loyalty Pengaruh Kepercayaan dan Kepuasan Konsumen Terhadap Loyalitas Konsumen - Ilham, Muhamad; F.C.Oentoeng, Irvan (JURNAL MANAJEMEN BISNIS TRI BHAKTI, 2024)
The rise of e-commerce has also changed people's shopping patterns. They no longer often visit shops or shopping centers to buy necessities but are starting to rely on shopping via e-commerce. This is what causes consumer confidence to decrease and they prefer other service places compared to this service place. The research design used in this research is quantitative research. In this research, the results of the R square correlation test were 0.717, showing that consumer loyalty is influenced by consumer trust and satisfaction at the Adi Computer Store by 71% while the remaining 29% is influenced by other factors or variables. Trust (X1) has a positive effect on Consumer Loyalty (Y ). This can be proven by the regression coefficient value of 0.613 and the t_count value of 8.784 ? t_(table) 1.660 and the significance value of 0.000 ? 0.05. Satisfaction (X2) has a positive effect on Consumer Loyalty (Y). This can be proven by the regression coefficient value of 0.147 and the t_count value of 1.587 ? t_(table) 1.660 and the significance value of 0.000 ? 0.05. This shows that the lower the satisfaction given, the lower the satisfaction felt by consumers. Trust (X1) and Consumer Satisfaction (X2) have a positive effect on Consumer Loyalty (Y). This can be proven by the calculated f_value of 128.905 ? f_table 3.09 and with a significance value of 0.000 ? 0.05.